Endotoxin‐stimulated Rat Hepatic Stellate Cells Induce Autophagy in Hepatocytes as a Survival Mechanism. Issue 1 (28th September 2015) - Dangi, Anil; Huang, Chao; Tandon, Ashish; Stolz, Donna; Wu, Tong; Gandhi, Chandrashekhar R.
Abstract : Bacterial lipopolysaccharide (LPS)‐stimulated hepatic stellate cells (HSCs) produce many cytokines including IFNβ, TNFα, and IL6, strongly inhibit DNA synthesis, but induce apoptosis of a small number of hepatocytes. In vivo administration of LPS (up to 10 mg/mL) causes modest inflammation and weight loss in rats but not mortality. We determined whether LPS‐stimulated HSCs instigate mechanisms of hepatocyte survival. Rats received 10 mg/kg LPS (i.p.) and determinations were made at 6 h. In vitro, HSCs were treated with 100 ng/mL LPS till 24 h. The medium was transferred to hepatocytes, and determinations were made at 0–12 h. Controls were HSC‐conditioned medium or medium‐containing LPS. LPS treatment of rats caused autophagy in hepatocytes, a physiological process for clearance of undesirable material including injured or damaged organelles. This was accompanied by activation of c‐Jun NH2 terminal kinase (JNK) and apoptosis of ∼4–5% of hepatocytes. In vitro, LPS‐conditioned HSC medium (LPS/HSC) induced autophagy in hepatocytes but apoptosis of only ∼10% of hepatocytes. While LPS/HSC stimulated activation of JNK (associated with cell death), it also activated NFkB and ERK1/2 (associated with cell survival). LPS‐stimulated HSCs produced IFNβ, and LPS/HSC‐induced autophagy in hepatocytes and their apoptosis were significantly inhibited by anti‐IFNβ antibody. Blockade of autophagy, on the other hand, strongly augmented hepatocyte apoptosis. While LPS‐stimulated HSCs cause apoptosis of a subpopulation of hepatocytes by producing IFNβ, they also induce cell survival mechanisms, which may be of critical importance in resistance to liver injury during endotoxemia. J. Cell. Physiol. 230: 94–105, 2016. © 2015 Wiley Periodicals, Inc.